2021
DOI: 10.1371/journal.pone.0251998
|View full text |Cite|
|
Sign up to set email alerts
|

High-dose drug heat map analysis for drug safety and efficacy in multi-spheroid brain normal cells and GBM patient-derived cells

Abstract: To test the safety and efficacy of drugs via a high does drug heat map, a multi-spheroids array chip was developed by adopting a micropillar and microwell structure. In the chip, patient-derived cells were encapsulated in alginate and grown to maturity for more than 7 days to form cancer multi-spheroids. Multi-spheroids grown in conventional well plates require many cells and are easily damaged as a result of multiple pipetting during maintenance culture or experimental procedures. To address these issues, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, in the pillar plate, because the spheroid is stably suspended at the end of the pillar tip by bonding with the hydrogel, fresh media change and drug screening are possible with only one stamping, thereby offsetting the need for labor-consuming pipetting. Our research team has previously reported various 3D-HTS analysis data using pillar plates and micropillar/well chips 17 22 . In particular, an aggregated spheroid model (ASM) that maximized drug efficacy evaluation by recapitulating the tumor microenvironment was attempted and reported in hepatocellular carcinoma (HCC) 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the pillar plate, because the spheroid is stably suspended at the end of the pillar tip by bonding with the hydrogel, fresh media change and drug screening are possible with only one stamping, thereby offsetting the need for labor-consuming pipetting. Our research team has previously reported various 3D-HTS analysis data using pillar plates and micropillar/well chips 17 22 . In particular, an aggregated spheroid model (ASM) that maximized drug efficacy evaluation by recapitulating the tumor microenvironment was attempted and reported in hepatocellular carcinoma (HCC) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…various 3D-HTS analysis data using pillar plates and micropillar/well chips [17][18][19][20][21][22] . In particular, an aggregated spheroid model (ASM) that maximized drug efficacy evaluation by recapitulating the tumor microenvironment was attempted and reported in hepatocellular carcinoma (HCC) 23 .…”
mentioning
confidence: 99%
“…Molecular and patient data are publicly available and published by Stringer et al [ 27 ]. A normal human astrocyte cell line was purchased from Gibco™, USA as a way to test the CNS toxicity of tested drugs [ 51 , 52 ]. Use of human cell lines was approved by the University of Newcastle’s Human Research Ethics Committee (Ref No.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular and patient data are publicly available and published by Stringer et al 18 . A normal human astrocyte cell line was purchased from Gibco TM , USA as a way to test the CNS toxicity of tested drugs 19,20 . Use of human cell lines was approved by the University of Newcastle’s Human Research Ethics Committee (Ref No.…”
Section: Methodsmentioning
confidence: 99%